Socioeconomic position, built environment and physical activity among children and adolescents: a systematic review of mediating and moderating effects - Oddbjørn Klomsten Andersen; Mekdes Kebede Gebremariam; Elin Kolle; Jakob Tarp (BMC, 2022)
Abstract Background Physical activity behaviors among children and adolescents are socioeconomically patterned. Understanding if, and how, the built environment contributes to socioeconomic inequalities in physical activity and for whom built environments are most important, can lead to the identification of intervention entry points to reduce inequalities in physical activity. Objective To summarize the existing evidence among children and adolescents on (a) whether the built environment mediates the association between socioeconomic position and physical activity and (b) whether socioeconomic position moderates the association between the built environment and physical activity. Methods A systematic literature search was conducted using PubMed, Embase, PsycINFO and Web of Science. Two independent reviewers screened articles for eligibility, extracted information from included studies and assessed risk of bias with the Quality Assessment Tool for Observational Cohort and Cross-Sectional studies. We performed a narrative evidence synthesis considering the totality of the evidence and by study characteristics such as geographic region, age group, and exposure-outcome assessment methodology. The reporting was conducted in agreement with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement. Results A total of 28 papers were included. In general, the studies were of low methodological quality. There was no evidence to support that the built environment functions as a mediator in the relationship between socioeconomic position and physical activity. We observed inconclusive moderation patterns with five studies reporting stronger associations between features of the built environment and physical activity among high socioeconomic positioned youths. Seven studies reported stronger associations among low socioeconomic positioned youth and fourteen studies reported no difference in associations. We observed different moderation patterns across geographical regions (Europe vs. US) indicating that, in Europe, having a walkable neighborhood is important for low socioeconomic positioned youth only. No differences in moderation patterns were observed for younger vs. older children or activity domains. Conclusion Current evidence does not support a strong interplay between built environment and socioeconomic position on physical activity in youth. However, given the low quality of the evidence, firm conclusions cannot be made, and additional high-quality research is likely to have substantial impact on the evidence base.